Is there a relation between Tefal’s communication strategy and the consumer’s decision making process? - Haász, Alexia; Lhotáková, Markéta, 1971-; Kožušníková, Eva; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis examines the relations between consumers decision making and Tefal brand's communication strategy. Consumers decision making depends on many different aspects: their knowledge, preferences, demographical background as well as their education and economical status. Tefal positions itself as a premium brand, and leverages it in its communication strategy. This thesis is examining if Tefal brand efficitently communicates about sustainability, price and quality, as well as how their communication strategy influences customers decision making process.
Vedoucí práce: Markéta Lhotáková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses